Design and performance of nutrient dosing control system for hydroponic chilli plant using fuzzy logic controller - Haryo Prastono; Mohamad Solahudin; Supriyanto Supriyanto (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2025)
The application of irrigation and nutrient provision is crucial for cultivating plants using hydroponic systems. This significance arises from the absence of natural nutrients in hydroponic growing media, which necessitates precise and tailored nutrient administration. This study aimed to discuss the design and construction of a nutrient dosing system employing both an on-off-based nutrient mixing control and a fuzzy logic-based fertigation control. Nutrient dosing system design entails establishing design criteria, functional and structural design, prototyping, programming, and testing. Performance testing involved a mixture of cocopeat and rice husk charcoal growing medium, with a 2-month-old chilli plant as the testing subject. The nutrient mixing control system resulted in a ready-to-use nutrient solution with a concentration of 1538.45 ppm, which slightly deviated from the 1500 ppm target. The total time required for nutrient mixing amounted to 3685.8 seconds. The calculations revealed a percentage error of 2.56 % for this nutrient mixing control system. The tested fertigation control system successfully maintained the moisture content of the growing medium within the available water zone with an error rate of 2.17 %. Observations over three days demonstrated that the control system activated fertigation processes twice daily, predominantly in the morning and evening. The total volume of fertigation administered ranged from 217 cm3 to 287 cm3 daily. All the components of the nutrient dosing system functioned effectively and performed well.